ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL MATERI LIMIT FUNGSI DENGAN METODE NEWMAN (NEWMAN ERROR ANALYSIS). - Firman Nur Diansyah; Ade Rohayati (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2025)
This study was motivated by the results of a literature review conducted by the researcher, in which a study at SMAN 1 Kasihan involving 49 students from Class XI IPA 1 and Class XI IPA 2 found that students had difficulty with the topic of limits of functions. One way to reduce students’ errors in this topic is to analyze the errors they make when answering limit problems. This study aims to identify the types of errors students make when solving limit problems. As this is a qualitative study, the method used is qualitative descriptive analysis. The research was conducted online with three 11th-grade science students in their second semester in the Bandung area during the 2019–2020 academic year. This error analysis is based on Newman’s (Newman Error Analysis). According to Newman, students’ errors in answering problems are categorized into five types: (1) reading errors (Reading Errors), (2) comprehension errors (Comprehension Errors), (3) transformation errors (Transformation Errors), (4) process skills errors (Process Skills Errors), and (5) encoding errors (Encoding Errors). The research instrument consisted of five validated questions. The results obtained in this study indicate that the types of errors made by students in solving problems on the topic of limits of functions include comprehension errors, transformation errors, and process skills errors.